The Effect of Using Crossword Puzzle Model on Learning Interest in Indonesian Learning Based On Students' Literacy - Muh Khaedar; Syamsul Alam (JED (Jurnal Etika Demokrasi), 2023)
Well-designed learning media will be more assist students in achieving high learning outcomes. However, the facts on the ground show that teachers have not optimally used instructional media so that students tend to get low learning outcomes. This study aims to determine the effect of using the Crossword Puzzle Model on students' learning outcomes in learning Indonesian. This research used an experimental study with a quasi-experimental method which was analyzed with distributive analysis and inferential analysis which aims to determine the effect of using the Crossword Puzzle model on learning outcomes of Indonesian language for the third grade students of SD Inpres Sero Gowa. The population in this study was all the third class and the sample in this study were 35 students of class III. The instrument for collecting data is carried out using statements that must be answered by respondents related to the questionnaire. The form of the questionnaire to measure students' learning outcomes is multiple choice. Technique Data analysis was used to examine the truth of the proposed hypothesis based on the variables studied, namely descriptive data analysis and inferential data analysis. Research result showed that there is an effect of using the crossword puzzle model on students' learning outcomes in learning Indonesian by obtained t-count t-table or 5.52 1.68488, it found that H0 was rejected and H1 was accepted, which means that crossword puzzle learning has an effect on Indonesian language learning outcomes in third grade students of SD Inpres Sero Gowa. It can be concluded that there is a significant impact of crossword puzzle media on students' learning outcomes in learning Indonesian in class III SD Inpres Sero Gowa.